Drug Abuse Peer Group Pressure and Deviant Behaviour of Students in Government Tertiary Institutions in Akwa Ibom State, Nigeria - Udoinyang, Nathan; Umoh, Salamat Amos (MultiTech Publisher, 2024)
This research investigated drug abuse, peer group pressure and deviant behaviour of students in government tertiary institutions in Nigeria using Akwa Ibom State as a case study. Survey method were used to collect data from the population of ten government tertiary institutions in Akwa Ibom State which was estimated as 194,071 by NUC and NBTE as of 2018 and 2023 respectively. With a mean criterion of 3.0, the statistical tools of the Statistical Package for the Social Sciences (SPSS) were used to analyse the study. Reviewing how drug abuse, peer group pressure, home and society base factors contribute to deviant behaviour of students in government tertiary institutions are: truancy, armed robbery, criminality, gangsterism, violet secret cult, divorce, parental arrogant, marital conflict and poor parent-child relationship. The study also shows that bad company of friends, wrong advice from friends and quest to belong to a particular class etc. are the extent to which peer group pressure contribute to drug abuse. The study concluded that students are the product of the home and society, the home family and society need to put in more effort in order to imbibe the right values and attitude to their child wards by been a good role model to them for the good of the home family and society as a whole. The study gave some relevant recommendations to parents, institutions, government and the entire society of Nigeria.